Effects of 4 weeks of whole-body vibration training on energy expenditure during deep squats of male well-trained students - Xiaohan Huang; Zhengyang Ye; Zhengyang Ye; Xuelin Qin (Frontiers in Physiology, 2023)
From the perspective of energy expenditure, this study investigated the effects of whole-body vibration training on the energy metabolism of deep squats with different weights. Twenty-two healthy male college students with sports experiences were selected and randomly assigned to perform resistance exercise vibration (REV) or resistance exercise (RE) with varying loads two times per week for 4 weeks. Oxygen uptake and heart rate were measured before, during, and after exercises using a gas analyzer, and energy expenditure was calculated. The results showed the following: 1) the oxygen uptake and energy expenditure of the REV group were significantly higher than those of the RE group during and 30 min after exercise (p < 0.01), respectively, and the excess post-exercise oxygen consumption (EPOC) was also significantly higher than that of the RE group (p < 0.01). 2) Changes in the oxygen uptake and energy expenditure were stable with increasing exercise in both vibration and non-vibration conditions. There was no difference in energy expenditure per unit of body mass versus additional energy per kilogram of body weight (p > 0.05). 3) No significant differences in changing exercise intensity were observed in the REV group compared to those in the RE group during the adjacent incremental load phases of △ (40%–0%) and △ (80%–40%) of load during and 30 min after exercise (p > 0.05). Our results suggest that 1) vibration training can increase energy expenditure during low-intensity training and excess post-exercise oxygen consumption, and improve the exercise intensity. 2) The effects on energy expenditure were the same for both weight-bearing and non-weight-bearing deep squats, up to 40% of body mass.